2016
DOI: 10.1159/000450787
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse in Nursing Homes: Do Special Care Units Make a Difference? A Secondary Data Analysis of the Swiss Nursing Homes Human Resources Project

Abstract: Background: In special care units (SCUs) for residents with advanced dementia, both personnel and organizations are adapted to the needs of residents. However, whether these adaptations have a preventive effect on elder abuse has not yet been explored. Objective: To describe the prevalence of observed emotional abuse, neglect, and physical abuse in Swiss nursing homes, to compare SCUs with non-SCUs concerning the frequency of observed emotional abuse, neglect, and physical abuse, and to explore how resident-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 43 publications
1
37
0
2
Order By: Relevance
“…Psychological abuse is reported as the most prevalent type of abuse in many studies [21,25,[27][28][29], and we also found a high prevalence rate of both observed and perpetrated psychological abuse. The most frequently reported act in our study was staff yelling at a resident, which is consistent with prevalence rates reported by nursing home staff in the Czech Republic [29] and by nurses in German nursing homes [27], but quite in contrast to the low rate found in Irish nursing homes [24].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Psychological abuse is reported as the most prevalent type of abuse in many studies [21,25,[27][28][29], and we also found a high prevalence rate of both observed and perpetrated psychological abuse. The most frequently reported act in our study was staff yelling at a resident, which is consistent with prevalence rates reported by nursing home staff in the Czech Republic [29] and by nurses in German nursing homes [27], but quite in contrast to the low rate found in Irish nursing homes [24].…”
Section: Discussionsupporting
confidence: 72%
“…Different data collection methods are also a significant cause of the variability in estimates, where most measurement instruments are self-designed and studyspecific [12]. The use of different reference periods might also impact the prevalence, where some studies use a four week period [25], while others use three months [21][22][23] or even the entire work career [26]. Nevertheless, a past-year reference period is the most commonly used [24,[27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of perpetrators were male workers [4,15], and mistreatment was related to their level of education and nursing care skills [16,17]. There are no consistent findings between period of work and mistreatment.…”
Section: Staff Traitsmentioning
confidence: 99%
“…Other studies reported that a shorter work period increases abusive behavior [18]. Abusive behaviors were closely associated with a high workload and levels of work stress [15,19]. Previous studies conducted a survey of care workers working in a nursing home or group home to determine the relationship between the work environment factors and care workers' awareness of mistreatment and abusive behavior [17,20].…”
Section: Staff Traitsmentioning
confidence: 99%